ПРАВОВОЕ РЕГУЛИРОВАНИЕ ПРЕДОСТАВЛЕНИЯ ГОСУДАРСТВЕННЫХ УСЛУГ В РЕСПУБЛИКЕ КАЗАХСТАН (Journal of actual problems of jurisprudence, 2019)
It is considered the problem of legal regulation of public services in the Republic of Kazakhstan, revealed the conceptual approaches to thedefinition of public services, the main directions of reforming public services.